Frederick M. Rener - Janez Stanonik (Acta Neophilologica, 1993)
The editors of Acta Neophilologica announce deeply grieved the demise of one of their major coworkers, Professor Frederick M. Rener. He was one of those intellectuals who after the Second World War emigrated from  Slovenia to America where they made distinguished scholarly careers at the universities of Canada and United States.